Impact of Information and Communication Technology (ICT) on Human Resource Management (HRM) in Bayelsa State Post Primary School Board - Yidougha Esido (JOURNAL OF PUBLIC ADMINISTRATION AND SOCIAL WELFARE RESEARCH, 2026)
This study assessed the impact of Information and Communication Technology (ICT) on Human Resource Management (HRM) in the Bayelsa State Post Primary School Board (BSPPSB). Specifically, the study examined the level of ICT adoption in HRM processes, evaluated the impact of ICT on HRM functions, and identified the challenges hindering the effective use of ICT within the Board. A descriptive survey research design was adopted for the study. The population comprised 58 staff members directly involved in HRM and ICT-related activities in the Board. Using the Krejcie and Morgan sample size determination table, a sample size of 48 respondents was selected through simple random sampling. Primary data were collected through a structured questionnaire, of which 42 copies were successfully retrieved and analyzed, representing a response rate of 87.5%. Data were analyzed using descriptive statistics, including frequencies, percentages, mean scores, and standard deviations. The findings revealed that ICT was highly adopted in staff record management through the use of computers, while its application in communication, performance appraisal, and promotion management was moderate. The study further found that ICT improved HRM functions by reducing recruitment and deployment time, enhancing record management, and assisting in the identification of ghost workers. However, challenges such as inadequate power supply, insufficient ICT facilities, and limited ICT training among HR personnel hindered effective ICT utilization. The study concluded that ICT has positively influenced HRM operations in BSPPSB, although infrastructural and capacity-related challenges must be addressed to achieve optimal benefits from ICT integration.